ASSESSING THE READINESS OF THE INDONESIAN OMBUDSMAN FOR IMPLEMENTING DATA-DRIVEN DECISION MAKING - Patnuaji Agus Indrarto; Eko Prasojo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Ombudsman of the Republic of Indonesia increasingly faces demands to base judgments on reliable evidence, yet many remain constrained by fragmented information systems and uneven analytical practices. This study addresses the practical problem of how prepared the Ombudsman of the Republic of Indonesia is to adopt data-driven decision making (DDDM), and the conceptual problem of limited understanding of how DDDM manifests within external complaint-handling bodies. The research employs the DECAS framework, which conceptualizes DDDM across five dimensions (Decision-Making Process, Decision Maker, Decision, Data, and Analytics) to assess organizational readiness. A qualitative exploratory design was used, drawing on nine semi-structured interviews with senior leaders, technical units, and regional representatives. Directed content analysis was applied to evaluate routines, data governance, and analytical capabilities. Findings show that although data increasingly support operational monitoring, leadership-level decisions still rely heavily on intuition due to descriptive, inconsistent, and siloed information. Analytical fluency varies across organizational tiers, and workflows for preparing and synthesizing data remain manual. Despite managing extensive datasets and expanding its digital infrastructure, the institution has not yet reached maturity for systematic DDDM. The study concludes that strengthened protocols, improved data governance, and more integrated analytical capacity are essential for enabling consistent evidence-based oversight.